Artificial Intelligence in Educational Leadership: Strategic, Analytical, Interactive, and Decision-Making Applications for the Digital Age - Sirat, Abdul Wali; Hakimi, Musawer; Himmat, Bilal; Enayat, Wahidullah (Jurnal Ilmiah Telsinas, 2025)
AI (artificial intelligence) is becoming an increasingly important factor in educational leadership by sharpening organizational strategy, analytical decision-making, interaction, and creativity. This article aims to systematically review AI applications in educational leadership contexts that can help both leaders and followers identify significant opportunities, challenges, or outcomes as part of effective leadership practice in a digital age. A qualitative systematic literature review was conducted using several credible databases (IEEE Xplore, Science Direct, MDPI, Wiley Online Library, Web of Science) and included work published from 2018 to 2025. A search strategy was developed to include specific keywords pertaining to AI and educational leadership along with peer-reviewed and English language studies. After applying stringent inclusion and exclusion criteria during the review, 35 studies were selected and analyzed in depth. The analysis points to the possibilities of AI to boost strategic planning, efficiency in resource allocation, predictive decision making, performance monitoring and evidence-based supportive approaches to personalized learning. AI opens up intentions and engagements between leaders, educators, and learners, and serves as an evidence-based resource for leader innovation in practice. The review and commentary also highlight key issues for research and practice, namely the ethical implementation of AI in education, methodological rigor, and transparency in reporting effects, and the critical role of human and AI collaborative tandem as a leadership practice for maximization. In conclusion, AI has the potential to advance educational leaders' effectiveness toward more efficient, informed, and innovative models, while also informing research and practice implications.